A future without walls : confronting our divisions - Snyder, T. Richard, 1936- (Fortress Press, 2021)
A Future without Walls offers a comprehensive and complex analysis of Othering, while unveiling the connections between our divisions and the roots, forms, and consequences of the walls that have been erected. The dividing walls are more than a problem calling for a quick fix. They are embedded in both our history and our current culture and demand fundamental transformation. The book offers concrete steps forward to help us dismantle these walls.